STRATEGI KOMUNIKASI PEMASARAN BUKALAPAK DALAM IKLAN BUKA REJEKI VERSI RAMADHAN MELALUI MEDIA YOUTUBE - Ilham Taufiqir Rahman, (2020)
Information and Technology (IT) is growing rapidly and is not limited to its spread. Many things that need to be understood by people in managing information, can be interpreted as media, which is a medium of communication media that plays a role in influencing the change of society. The internet is capable of giving birth to a new network that is familiar with social media mentions. Social media is an online media that makes it easy for people to participate, share, and create content including blogs, social networks, WiFi, forums and virtual worlds. The study took Bukalapak's advertisement on Youtube media because the Bukalapak data was ranked 3rd in 10 e-commerce with the largest visitors in 2019. A total of 42.9 million visitors in a year were able to outperform the e-commerce below. Bukalapak is still a consumer favorite in online buy and sell transactions. Using a qualitative approach of descriptive studies or in-depth interviews using the concept of communication strategies with a focus on Bukalapak's advertisement for Ramadan is open. This study resulted in the conclusion that the marketing communication strategy applied in accordance with the purpose of Bukalapak. Bukalapak already compiled a few steps of communication strategy and Bukalapak is an e-commerce known by the wider community through advertising in social media and the strategies used are seen from geografitation segmentation, Demographic segmentation, Psychographic segmentation.